2021
DOI: 10.3389/fonc.2021.582694
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria’s Role in the Maintenance of Cancer Stem Cells in Glioblastoma

Abstract: Glioblastoma (GBM), one of the deadliest primary brain malignancies, is characterized by a high recurrence rate due to its limited response to existing therapeutic strategies such as chemotherapy, radiation therapy, and surgery. Several mechanisms and pathways have been identified to be responsible for GBM therapeutic resistance. Glioblastoma stem cells (GSCs) are known culprits of GBM resistance to therapy. GSCs are characterized by their unique self-renewal, differentiating capacity, and proliferative potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 91 publications
(93 reference statements)
0
24
0
Order By: Relevance
“…5 ). This finding bridges the function of Par3 with a relatively well-established field of GBM metabolism, which has been shown to depend on mitochondrial action, glucose oxidation, and glycolysis at least in mice bearing GBM tumors [ 43 ], and in various studies of human GBM [ 44 ]. Furthermore, human GBMs with stem-like characteristics appear to generate their ATP via mitochondrial oxidative phosphorylation in parallel to the generation of ROS [ 45 ].…”
Section: Discussionmentioning
confidence: 62%
“…5 ). This finding bridges the function of Par3 with a relatively well-established field of GBM metabolism, which has been shown to depend on mitochondrial action, glucose oxidation, and glycolysis at least in mice bearing GBM tumors [ 43 ], and in various studies of human GBM [ 44 ]. Furthermore, human GBMs with stem-like characteristics appear to generate their ATP via mitochondrial oxidative phosphorylation in parallel to the generation of ROS [ 45 ].…”
Section: Discussionmentioning
confidence: 62%
“…It has been evidenced that CSCs activate mitochondrial stress pathways in response to stressors such as radiation, chemotherapy, or hypoxia. This contribution is multidimensional by regulating stemness, quiescence, and treatment resistance 85 . Recent studies on glioblastoma stem cells (GSCs) demonstrated the pivotal role of mitochondria in GSCs biology.…”
Section: Cancer Stem Cells Can Be Defeated By Targeting Mitochondriamentioning
confidence: 99%
“…CSCs are often quiescent with the ability for self-renewal and proliferative potential. They also show a high capacity to switch quickly between glycolysis and OXPHOS [22]. Although some of the CSCs such as breast, ovarian cancers or glioblastoma [23][24][25] rely on glycolysis as the predominant metabolic pathway, it is now more widely accepted that most CSCs use OXPHOS as their preferred mechanism of energy acquisition.…”
Section: Use Of Glycolysis and Oxphos By Cancer Cellsmentioning
confidence: 99%